Geriatric Anesthesiology (Springer International Publishing, 2018)
Surgical and anesthetic techniques have evolved to allow a growing number of older adults to undergo surgery, and current estimates are that 50% of Americans over the age of 65 years old will have an operation. However, as the knowledge regarding perioperative care of the elderly surgical patient grows, so do the questions. In this edition, each chapter includes a section entitled "Gaps in Our Knowledge," meant to highlight areas in which research is needed, as well as hopefully inspire readers to begin solving some of these questions themselves. Building upon the strong foundation of the first two editions, Geriatric Anesthesiology, 3rd edition also assembles the most up-to-date information in geriatric anesthesia and provides anesthesiologists with important new developments.Topics covered include several new chapters that reflect the evolution of multidisciplinary geriatric care throughout the perioperative continuum, as well as the growing body of literature related to prehabilitation. In addition, discussion of the surgeon's perspective and geriatrician's perspective on surgery in the geriatric population is covered, as well as the systematic physiologic changes associated with aging and the pharmacologic considerations for the geriatric patient undergoing procedures. Finally, the last section discusses postoperative care specific to the geriatric population, including acute pain management, ICU management, recent evidence and up-to-date practice regarding delirium and postoperative cognitive dysfunction, and palliative care. .